CLINICAL AND LABORATORY STUDY OF THE EFFECTIVENESS OF VARIOUS ANTIMICROBIAL DRUGS IN THE TREATMENT OF PERIODONTITIS - Azizabonu Akhmadovna Kodirova; Khasanova Dilnoza Akhrorovna (Modern American Journals, 2025)
Periodontitis is a chronic inflammatory disease affecting the supporting structures of the teeth, leading to progressive destruction of the periodontal ligament and alveolar bone. The present study aims to evaluate and compare the clinical and laboratory efficacy of different antimicrobial agents used in the treatment of periodontitis. A total of 90 patients diagnosed with moderate to severe periodontitis were enrolled and divided into three groups. Each group received standard mechanical debridement in combination with one of the antimicrobial therapies: chlorhexidine, metronidazole, or doxycycline. Clinical parameters including probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP) were assessed. Microbiological analysis was conducted to determine bacterial reduction. The results demonstrated significant improvement in all groups, with the doxycycline group showing superior clinical and microbial outcomes. This study highlights the importance of selecting appropriate antimicrobial therapy based on both clinical presentation and microbiological findings.
Keywords: Periodontitis, antimicrobial therapy, chlorhexidine, metronidazole, doxycycline, clinical outcomes, microbiological assessment